FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN CINA BERKUNJUNG KE BALI - Inayatuka, Vina; Sukawati, Tjokorda Gede Raka (E-Jurnal Manajemen; Vol 8 No 5 (2019)DO - 10.24843/EJMUNUD.2019.v08.i05.p08, 2019)
This research was conducted in Bali involving 80 respondents who were Chinese tourists who were visiting Bali with non-probability sampling method. Data was collected through questionnaires. The data analysis technique used is factor analysis. Based on the analysis found five factors that influence Chinese tourists visiting Bali, these five factors explain all variants in the data that is 62,049 percent. The five factors include the process (which consists of variable prices, physical facilities, promotion, distribution, people and products), lifestyle (which consists of variables of age, occupation and income), friends (consisting of group variables, family, and social status), culture (which consists of social and sub-cultural class variables) and motivation (which consists of perception variables), motivation is the most dominant variable. Keywords: service marketing mix, culture, chinese tourists